The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1063/1.349671
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ion-solid interaction in ion-beam-induced deposition of gold

Abstract: Gold films were deposited on quartz-crystal microbalances by decomposing C7H7F6O2Au (dimethyl gold hexafluoroacetylacetonate) with 2–10-keV Xe+, Kr+, Ar+, Ne+, or He+ ion beams. The number of molecules decomposed per incident ion (i.e., the total decomposition yield) was determined as a function of ion mass and energy. The total decomposition yield increases with increasing ion mass and ion energy, and is approximately proportional to the nuclear stopping power. A binary collision model and a thermal spike mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 24 publications
0
54
0
Order By: Relevance
“…So far, almost all IBID work is performed with Ga + focused ion beams (FIB), which have at best a probe size of 5 nm [3]. Only a few studies deal with broad (∼mm) noble-gas ion beams, like He + , Ne + and Xe + [4,5]. Despite the small probe size, structures grown with a stationary FIB-i.e.…”
Section: Introductionmentioning
confidence: 99%
“…So far, almost all IBID work is performed with Ga + focused ion beams (FIB), which have at best a probe size of 5 nm [3]. Only a few studies deal with broad (∼mm) noble-gas ion beams, like He + , Ne + and Xe + [4,5]. Despite the small probe size, structures grown with a stationary FIB-i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Low energy noble gas ion beams have been applied as an effective tool to modify surface structures and properties on various materials at the nanoscale [7][8][9][12][13][14][15]. Here we present ion beam sculpting results for a variety of noble gas ions and ion beam fluxes to drastically change some of the potentially relevant parameters of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Dubner et al found that the deposition yield is proportional to the calculated stopping power and, consequently, explained IBID in terms of the energy transfer via a cascade of atom-atom collisions to adsorbed precursor molecules. 4,5 Chen et al measured different angular dependences of the deposition and sputtering yields, which suggests that IBID cannot be explained solely in terms of ion-solid interactions. 6 Lipp et al supported the secondary electron model, having observed a linear relationship between the deposition yield and the secondary electron yield within the ion energy range of 10-30 keV.…”
Section: 2mentioning
confidence: 99%